PENGARUH TOTAL QUALITY MANAGEMENT SISTEM AKUNTANSI MANAJEMEN DAN SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL (Study Empiris di Perusahaan Jasa Wilayah Surakarta) - Sugiyatno, Rispantyo & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
The study aims to test hypotheses about the influences of Total QualityManagement, accounting systems management (SAM) and reward systems tomanagerial performance services company Surakarta. The type of data in this studyare primary data, method of data collection is done by distributing questionnaires bypurposive sampling method. The sample used in this study is the staff in theaccounting division with four sample services company in the region Surakarta with35 respondents. The analytical method used in this research is multiple regressionanalysis. Results of the analysis showed that the (1) Total Quality Management havea significant effect on managerial performance, (2) Management Accounting Systemsignificantly influence managerial performance, and (3) award system but nosignificant effect on managerial performance.Keywords: Total Quality Management, Accounting System Management, ChoiceSystem, Managerial Performance.